Pengaruh Profesionalisme Kerja Aparatur Sipil Negara Terhadap Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gorontalo - Habi, Riska A.; Tahir, Arifin; Sulila, Ismet (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine whether the work professionalism of civil servant influences the quality of public services at the population and civil registration office of Gorontalo Regency and to assess the extent of this influence. This research employs a quantitative approach. Data collection techniques include observations and questionnaires with a sample size of 50 respondents. Data analysis techniques involve simple linear regression and coefficient of determination tests. The results indicate that the work professionalism of civil servants has a positive and significant Office of Gorontalo Regency, accounting for 43,5%. The remaining 56,5% is influenced by other variables not examined in this research.